2018
DOI: 10.1101/308916
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide CRISPR-dCas9 screens inE. coliidentify essential genes and phage host factors

Abstract: 13High-throughput genetic screens are powerful methods to identify genes linked to a given 14 phenotype. The catalytic null mutant of the Cas9 RNA-guided nuclease (dCas9) can be conveniently 15 used to silence genes of interest in a method also known as CRISPRi. Here, we report a genome-wide 16 CRISPR-dCas9 screen using a pool of ~ 92,000 sgRNAs which target random positions in the 17 chromosome of E. coli. We first investigate the utility of this method for the prediction of essential 18 genes and various unu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 74 publications
1
25
0
Order By: Relevance
“…Text 1). Our relative fitness values were correlated with previously reported measurements (18,19) but had greatly expanded dynamic range due to greater sequencing depth and a shorter growth period ( Fig. S6D-E, Sup.…”
supporting
confidence: 89%
“…Text 1). Our relative fitness values were correlated with previously reported measurements (18,19) but had greatly expanded dynamic range due to greater sequencing depth and a shorter growth period ( Fig. S6D-E, Sup.…”
supporting
confidence: 89%
“…We used 2 sgRNAs targeting each ORF; recent studies have shown that more are needed to ensure statistical significance when assessing gene essentiality 11 . For approximately 50% of the genes with high fitness scores in our data, one sgRNA was significantly depleted from the library and the other was not (Supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Since the protospacer region of sgRNAs is small enough (~ 20 nt) to be sequenced by NGS, it can serve as a barcode and allow monitoring of the abundance of each clone in the library. CRISPRi libraries have been applied to screen gene essentiality and diverse phenotypes including morphology, solvent tolerance, and phage resistance [9][10][11] . Inducible CRISPRi has been developed for several cyanobacteria strains 12,13 , but pooled sgRNA libraries have not been exploited.…”
Section: Introductionmentioning
confidence: 99%
“…pyogenes (Cong and Zhang, ), or (ii) a single gRNA (sgRNA) in short fusion form of tracrRNA and crRNA (Jinek et al , ). The immense majority of the already developed tools have utilized sgRNAs due to simplicity of working with a single RNA molecule (Zalatan et al , ; Deaner and Alper, ; Rousset et al , ). In general, the efficiency of using just sgRNA or both tracrRNA and crRNA was observed to be comparable – although the architecture of crRNA allows for a rapid and simple cloning strategy when generating multiplex crRNA arrays.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, we have developed a set of modular, composable vectors encoding CRISPRi systems using either (i) non-coding trans-activating CRISPR RNA (tracrRNA) and the CRISPR locus needed for CRISPR RNA (crRNA) generation, present in the native type II CRISPR/Cas9 system of S. pyogenes (Cong and Zhang, 2015), or (ii) a single gRNA (sgRNA) in short fusion form of tracrRNA and crRNA (Jinek et al, 2012). The immense majority of the already developed tools have utilized sgRNAs due to simplicity of working with a single RNA molecule (Zalatan et al, 2015;Deaner and Alper, 2017;Rousset et al, 2018). In general, the efficiency of using just sgRNA or both tracrRNA and crRNA was observed to be comparablealthough the architecture of crRNA allows for a rapid and simple cloning strategy when generating multiplex crRNA arrays.…”
Section: Introductionmentioning
confidence: 99%